Public Sector Accounting and Organizational Performance: Study in Indonesian Health Care Industry - Inggriani Elim; Aneke Wangkar; Treesje Runtu; Lady Diana Latjandu (Hasanuddin Economics and Business Review, 2022)
The implementation of public sector accounting is a crucial factor in improving the performance of public sector organizations. One of the organizations that implement public sector accounting is the health care industry. Purpose of this study to analyze public sector accounting effect on organizational performance in the health care industry. This research is quantitative research conducted at a health institution in Manado City. Respondents who participated were 100 participants from regional hospitals and health centers in Manado City, Indonesia. Data analysis is assisted by path analysis. The research findings reveal the relationship of public sector accounting to the performance of public sector organizations and the relationship mediated by accounting information systems. Several limitations and suggestions were revealed in this study.